Emergent Endoscopic Services for Acute Upper Gastrointestinal Bleeds: A Critical Need in Government Tertiary Care Hospitals - Khan, Shahzaib; Owais Khan (Journal of the Pakistan Medical Association, 2024)
Upper gastrointestinal bleeding (UGIB), defined as blood loss originating from above the ligament of Treitz in the gastrointestinal tract, is the most common gastroenterological emergency.1 Acute forms of UGIB have an approximate in-patient mortality rate of 2-10 percent, despite advances in management options over the last three decades. Urgent endoscopy within 12 hours is the standard management for all patients presenting with UGIB, both as a diagnostic and therapeutic tool.1 Worldwide, most cases of UGIB are due to peptic ulcers, however, this trend differs in Pakistan, where variceal haemorrhage is the predominant cause most likely due to the high disease burden of hepatitis C in the country2. According to the national health survey conducted in 2009, there is limited data on the exact prevalence and incidence, but trends have shown a frequency of 4.7% (CI 4.6-4.8), and around 8 million affected people.3 The major viral epidemic continues to impact the country’s healthcare system, primarily due to resource constraints, overburdened government setups, and lack of public awareness.2 As such, there is an urgent need to cater to this healthcare detriment, especially the decompensated forms of the disease which contribute to most mortalities.4 Like other low-income countries, Pakistan does not have the luxury of emergent endoscopic services and facilities in the well-developed world as a primary care modality. No national data on mortality from UGIB in Pakistan, or numbers on acute cases managed without emergent endoscopy exist. A study by Rajan et al 5 demonstrates that a lack of emergent endoscopy is an independent predictor of mortality among patients with UGIB in similar low-income setups, with numbers rising up to 30%. Such trends indicate a significant gap in our literature that needs to be addressed, with more studies oriented around this health concern. We also require a higher number of emergent endoscopic services to be made readily available, especially at large government tertiary care centers which cater to most of these patients, especially given the epidemic of Hepatitis C.